2013
DOI: 10.1111/jce.12293
|View full text |Cite
|
Sign up to set email alerts
|

Catheter‐Tissue Contact Force Determines Atrial Electrogram Characteristics Before and Lesion Efficacy After Antral Pulmonary Vein Isolation in Humans

Abstract: EGM characteristics do not reliably predict either CF before the onset of RF, nor do they predict the likelihood of an effective lesion. CF parameters were superior to power, temperature, and impedance changes during RF in predicting lesion efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 30 publications
(60 reference statements)
4
48
0
Order By: Relevance
“…31 Another acute study found that local FTI provided the highest sensitivity and specificity for effective PVI lesion creation. 32 A single center study also showed that an FTI >1200 g during PVI correlated with larger late gadolinium enhancement areas on 3 month post PVI magnetic resonance imaging scans. 33 In our laboratory, a minimum CF of 10 g is required for ablation targeting PVI or for linear atrial lesions.…”
Section: Real-time Cf Sensing: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…31 Another acute study found that local FTI provided the highest sensitivity and specificity for effective PVI lesion creation. 32 A single center study also showed that an FTI >1200 g during PVI correlated with larger late gadolinium enhancement areas on 3 month post PVI magnetic resonance imaging scans. 33 In our laboratory, a minimum CF of 10 g is required for ablation targeting PVI or for linear atrial lesions.…”
Section: Real-time Cf Sensing: Clinical Evidencementioning
confidence: 99%
“…9,32 Electrode temperature feedback from tissue heating is, however, largely neutralized or eliminated during open IT RF ablation, and the impedance measurements are sensitive to the many parameters that could affect any component of the typically large unipolar RF energy delivery circuit.…”
Section: Lesion Modeling Size Estimation and Predictionmentioning
confidence: 99%
“…10 In another study, a weak relationship was found between these parameters throughout the LA in paroxysmal AF patients, around half of whom were in AF, although the authors did not give details of how the electrogram parameters were measured. 11 This study examined this relationship in both AF and SR throughout the LA, using automated analysis of 8 s of electrogram data at each location.…”
Section: Catheter Contact and The Electrogrammentioning
confidence: 99%
“…Data from spectral analysis of electrograms to guide ablation 9 may also be of use, but the effect of catheter contact on these measurements is similarly unknown. In man, a higher CF is weakly correlated with increasing electrogram amplitude in the LA 10,11 and left ventricle. 12 In porcine studies, the orientation of the catheter also impacts on the bipolar electrogram morphology observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation